2019
DOI: 10.1001/jamaophthalmol.2019.2537
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in the Peripapillary Retinal Nerve Fiber Layer Thickness of Patients With Type 2 Diabetes

Abstract: IMPORTANCE Type 2 diabetes is expected to accelerate age-related peripapillary retinal nerve fiber layer (pRNFL) loss, but limited information on the rate of reduction in pRNFL thicknesses in patients with type 2 diabetes is available. OBJECTIVE To investigate longitudinal changes in pRNFL thickness in patients with type 2 diabetes, with or without diabetic retinopathy (DR). DESIGN, SETTING, AND PARTICIPANTS A total of 164 eyes of 63 healthy individuals and 101 patients with type 2 diabetes (49 patients withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 43 publications
4
53
4
Order By: Relevance
“…The results of this study were similar to our previous study, which studied pRNFL thickness using a similar study design 35 . The previous study determined that diabetic eyes had a significantly greater decrease in pRNFL over 3 years than normal eyes regardless of mild DR progression.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study were similar to our previous study, which studied pRNFL thickness using a similar study design 35 . The previous study determined that diabetic eyes had a significantly greater decrease in pRNFL over 3 years than normal eyes regardless of mild DR progression.…”
Section: Discussionsupporting
confidence: 90%
“…Although one study showed there was no signi cant changes of average or sectoral RNFL thicknesses in no-DR [30] , some other studies found RNFL loss may occur in no-DR [31,32].Our study showed that the temporal RNFL thickness in diabetic patients was signi cantly thinner than that in the normal group. Further analysis revealed that the temporal RNFL thickness in the no-DR group was signi cantly smaller than that in the normal group.…”
Section: Discussioncontrasting
confidence: 70%
“…In addition, glutamate accumulation induced by DRN increases the secretion of vascular endothelial growth factor, which leads to damage to the BRB. 28 Considering these mechanisms, DRN is a crucial factor in the development of DR, and it could explain the findings of the present and a previous study 13 of significant pRNFL loss in patients without DR.…”
Section: Figuresupporting
confidence: 60%
“…8 The most important characteristics of DRN involve reactive gliosis and neuronal apoptosis, which may predominantly affect the inner retinal layer. 9 Several studies have reported inner retinal injury associated with DRN, 8,[10][11][12] and we also reported progressive pRNFL thinning in diabetic patients with or without DR. 13 Because the prevalence of diabetes and myopia is increasing worldwide, 3,14 the number of diabetic patients with myopia is expected to increase in the future. Myopia causes pRNFL reduction, which may accelerate pRNFL loss in diabetic patients, but the effects of myopia on pRNFL thickness in diabetic patients have not been definitively evaluated.…”
mentioning
confidence: 99%